Living with the promise of violence the state and indigenous people in a militarized frontier - Gatmaytan, Augusto B. (Philippine Studies: Historical and Ethnographic Viewpoints, 2018)
Despite its significance in postwar Philippine history and its continuing relevance today, scholars have largely neglected militarization, especially as experienced by indigenous peoples. Drawing on fieldwork data from 2009 to 2010, this article outlines a phenomenology of the terror experienced by an indigenous community in Agusan del Sur province at the hands of state paramilitary forces involving their own datu. Neil Whitehead’s “poetics of violence” is applied to the analysis of the community’s understanding of the state and its violence. It ends with reflections on the relevance of the community’s experience in relation to issues of continuing “Lumad killings” and the rise in extrajudicial killings.